Recent progress on field-effect transistor-based biosensors: device perspective - Smaani, Billel; Nafa, Fares; Benlatrech, Mohamed Salah; Mahdi, Ismahan; Akroum, Hamza; walid Azizi, Mohamed; Harrar, Khaled; Kanungo, Sayan (Beilstein Journal of Nanotechnology, 2024)
Over the last few decades, field-effect transistor (FET)-based biosensors have demonstrated great potential across various industries, including medical, food, agriculture, environmental, and military sectors. These biosensors leverage the electrical properties of transistors to detect a wide range of biomolecules, such as proteins, DNA, and antibodies. This article presents a comprehensive review of advancements in the architectures of FET-based biosensors aiming to enhance device performance in terms of sensitivity, detection time, and selectivity. The review encompasses an overview of emerging FET-based biosensors and useful guidelines to reach the best device dimensions, favorable design, and realization of FET-based biosensors. Consequently, it furnishes researchers with a detailed perspective on design considerations and applications for future generations of FET-based biosensors. Finally, this article proposes intriguing avenues for further research on the topology of FET-based biosensors.
Keywords: biomolecule detection; biosensors; charge modulation; dielectric modulation; field-effect transistor